Atlas of Robotic Thoracic Surgery (Springer International Publishing, 2018)
This book represents the definitive robotic surgery atlas, containing didactic material necessary to facilitate effective practice in thoracic surgery and to provide learning tools in these methods both to practicing surgeons and to those in training. It defines the complete operative pathway for each procedure for surgeons who wish to be a complete robotic cardiothoracic surgeon and include hints and procedural pitfalls derived from the experiences of chapter contributors. The Atlas of Robotic Thoracic Surgery is illustrated with high quality illustrations and color photographs from surgical operations and contains expert analysis from leading surgeons who provide the key visual features of their chosen topics. Anesthetic and cardiopulmonary support preparation for each operation are included and selected references will be provided to emphasize evidence-based outcomes.This book has been designed to augment Atlas of Robotic Cardiac Surgery edited by Ranny Chitwood, both being developed from these same concepts of simplicity and practical instruction. It will therefore be an important resource for all involved in thoracic robotic surgery or interested in learning more about the techniques involved.